Making Panchayati Raj a reality - Indiresan, P.V. (1995)
"The Panchayati Raj Act should be redesigned to incorporate a structural bulwark to ensure its compliance, says the author. Panchayat officials should be protected from political interference in the normal discharge of their duties. Transparency and a total lack of secrecy is the essence of Panchayati Raj. Calling for a criminal-proof election system, he suggests that giving the voter a choice to reject all candidates would be a salutary provision which would force all parties to field only good candidates"
Keywords: India. Constitution - Amendments - 73rd; Panchayat - India